Nanocarrier-mediated CRISPR/Cas9 Gene Editing of BMP2 for Bone Repair - Divya Saini (International Journal of Advance in Molecular Engineering, 2025)
The growth factor that plays an important role in the formation and repair of bones is bone morphogenetic protein 2(BMP2). Nevertheless, because BMP2 is rapidly degrading and has less than half the time to live, its delivery into bone defects may be difficult. A plan to develop a nanocarrier via CRISPRCas9 gene editing mechanism for the delivery of BMP2 into bone defects is outlined in this research proposal. The system will use nanoparticles to encapsulate the CRISPR/Cas9 components and BMP2 gene and will target the delivery of the system to bone-forming cells. BMP2 clinical use is impeded by fast degradation of in vivo, which limits efficacy to a shorter period of time. In order to address these problems a new nanocarrier mediated, CRISPRCas9 gene editing system targeting BMP2 delivery for bone healing and repair is proposed in this research.
Keywords: BMP2 gene editing; Bone regeneration; CRISPR/Cas9 technology; Nanocarriers; Osteoblasts